Deciphering pyritization-kerogenization gradient for fish soft-tissue preservation - Oses, Gabriel L.; Petri, Setembrino; Voltani, Cibele G. [UNESP]; Prado, Gustavo M. E. M.; Galante, Douglas; Rizzutto, Marcia A.; Rudnitzki, Isaac D.; Silva, Evandro P. da; Rodrigues, Fabio; Rangel, Elidiane C. [UNESP]; Sucerquia, Paula A.; Pacheco, M. L. A. F. (Nature Publishing Group, 2017)
Soft-tissue preservation provides palaeobiological information that is otherwise lost during fossilization. In Brazil, the Early Cretaceous Santana Formation contains fish with integument, muscles, connective tissues, and eyes that are still preserved. Our study revealed that soft-tissues were pyritized or kerogenized in different microfacies, which yielded distinct preservation fidelities. Indeed, new data provided the first record of pyritized vertebrate muscles and eyes. We propose that the different taphonomic pathways were controlled by distinct sedimentation rates in two different microfacies. Through this process, carcasses deposited in each of these microfacies underwent different residence times in sulphate-reduction and methanogenesis zones, thus yielding pyritized or kerogenized soft-tissues, and a similar process has previously been suggested in studies of a late Ediacaran lagerstatte.